Performance of Ultrasonic-assisted Membrane Anaerobic System (UMAS) on Palm Oil Mill Effluent (POME) / Shafie N. F. A....[et al.] - N. F. A., Shafie; A. I. S., Rahman; A., Yahya; U. Q. A., Mansor; A. M., Som; A. H., Nour; Z., Hassan; R. M, Yunus (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Palm Oil Mill Effluent (POME) is hard wastewater that contains a high amount of Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD5), Total Suspended Solids (TSS) and Volatile Suspended Solids (VSS). These vital parameters should be treated first before it is discharged into any water ways. There are many treatment methods implied until this decade with traditional method. Pond system is the most implied method due to its low cost. The performance of Ultrasonic-assisted Membrane Anaerobic System (UMAS) is evaluated on the ability of UMAS to treat these parameters. The UMAS must be operated daily for 5 hours operation per day with 3 hours sonication. The experiment is done when the UMAS is achieving a steady state. The steady state is achieved on day 7 with no gas was generated. The performance of UMAS showed high COD removal efficiency with 98.7%. The kinetic study is also evaluated by implying three models which are Monod, Contois and Chen and Hashimoto model.